2009
DOI: 10.1158/1535-7163.mct-09-0262
|View full text |Cite
|
Sign up to set email alerts
|

Differential requirement for focal adhesion kinase signaling in cancer progression in the transgenic adenocarcinoma of mouse prostate model

Abstract: Increasing evidence indicates that adhesion signaling plays an important role in the tumor microenvironment, contributing to cancer progression, invasion, and metastasis. Focal adhesion kinase (FAK) is a nonreceptor protein tyrosine kinase that regulates adhesion-dependent cell signaling and has been implicated in mediating steps in cancer progression and metastasis in many human cancers, including prostate. We have investigated the role of FAK in the appearance of adenocarcinoma (atypical epithelial hyperplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
1
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 22 publications
1
45
1
1
Order By: Relevance
“…membrane, our results support the model that prostate tumors contain a basal compartment consisting of putative stem cells able to undergo self-renewal as well as transit-amplifying cells undergoing rapid proliferation. In agreement with the hypothesis that integrin β4 signaling plays a unique role in prostate tumorigenesis, others have shown that genetic ablation of FAK does not impair tumor initiation or progression to adenocarcinoma in PB-TAg mice (80), suggesting that the β1 integrin/FAK signaling axis does not contribute to prostate tumorigenesis.…”
Section: Figuresupporting
confidence: 72%
“…membrane, our results support the model that prostate tumors contain a basal compartment consisting of putative stem cells able to undergo self-renewal as well as transit-amplifying cells undergoing rapid proliferation. In agreement with the hypothesis that integrin β4 signaling plays a unique role in prostate tumorigenesis, others have shown that genetic ablation of FAK does not impair tumor initiation or progression to adenocarcinoma in PB-TAg mice (80), suggesting that the β1 integrin/FAK signaling axis does not contribute to prostate tumorigenesis.…”
Section: Figuresupporting
confidence: 72%
“…Recently, researchers started to carefully look into the molecular pathways involved in two lineages of carcinogenesis (different prostate lobes, mainly DLP and VP) in TRAMP mice after the lineage differences of the prostate carcinogenesis had been recognized [9,13]. For instance, Slack-Davis et al studied the requirement for focal adhesion kinase (FAK) signaling in cancer progression in TRAMP mice with C57BL/6 background [35]. They found that loss of FAK or its inhibition with PF-562271 (small molecular inhibitor for FAK) did not alter the progression to AHT.…”
Section: Molecular Changes In Prostate Carcinogenesis In Tramp Modelmentioning
confidence: 99%
“…The activation of FAK and Akt has been reported to be closely associated with cell proliferation, anoikis resistance, migration, invasion and stemness of PC cells. [27][28][29][30][31][40][41][42] CXCR4 leads to the activation of diverse intracellular signaling pathways including the Akt pathway, 34,43,44 and CXCL12 evoked increased expression of FAK and enhanced FAK phosphorylation. 35 Furthermore, it has been established that the tumorigenic and metastatic process of PC is regulated by CXCL12/CXCR4 axis.…”
Section: Discussionmentioning
confidence: 99%
“…Among these pathways, the activation of FAK and Akt has been reported to be closely associated with cell proliferation, anoikis resistance, migration, invasion and stemness of PC cells. [27][28][29][30][31] In PC3-shTpl2 cells, depletion of Tpl2 led to a remarkable decrease in the phosphorylation levels of FAK and Akt, compared with those of control cells (Fig. 5a).…”
Section: Fak and Akt Mediate Oncogenic Effects Of Tpl2 In Adi Pc Cellsmentioning
confidence: 93%
See 1 more Smart Citation